2013
DOI: 10.1016/j.vetpar.2012.08.009
|View full text |Cite
|
Sign up to set email alerts
|

The present status of anthelmintic resistance in gastrointestinal nematode infections of sheep in the northwest of Spain by in vivo and in vitro techniques

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 17 publications
1
32
0
1
Order By: Relevance
“…Although MOX resistance has been described before in Europe (Wilson and Sargison 2007, Scheuerle and others 2009, Sargison and others 2010, Martinez-Valladares and others 2013), this study confirmed a case of H contortus resistance to milbemycins and avermectins, MOX and DRM, in a sheep flock in Europe. Also, resistance to FBZ was found in this flock.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Although MOX resistance has been described before in Europe (Wilson and Sargison 2007, Scheuerle and others 2009, Sargison and others 2010, Martinez-Valladares and others 2013), this study confirmed a case of H contortus resistance to milbemycins and avermectins, MOX and DRM, in a sheep flock in Europe. Also, resistance to FBZ was found in this flock.…”
supporting
confidence: 81%
“…Nowadays, multiple anthelmintic resistance is of major concern for the sheep and goat industry (Sargison 2012). In Europe, resistance to moxidectin (MOX) has been described in Germany in Haemonchus contortus (Scheuerle and others 2009), in the UK in Teladorsagia circumcincta (Wilson and Sargison 2007, Sargison and others 2010), and recently to long-acting injectable MOX in northwestern Spain (Martinez-Valladares and others 2013), and is not as common as resistance to ivermectin (IVM) and doramectin (DRM) (Maingi and others 1997, Ambrosini 2000, Sargison and others 2001, Cernanska and others 2006, Borgsteede and others 2007). …”
mentioning
confidence: 99%
“…Moreover, countries which have publications on multiple cross-sectional studies over time, such as Brazil (Echevarria et al, 1996;SczesnyMoraes et al, 2010), New Zealand (Kettle et al, 1981;Waghorn et al, 2006) and the United Kingdom (Cawthorne and Cheong, 1984;Bartley et al, 2003;Mitchell et al, 2010), reported a worsening situation, with an increase both in AHR prevalence and in the number of GIN species affected. Multiple-drug resistance is also increasing (Sargison et al, 2007;Voigt et al, 2012;Martínez-Valladares et al, 2013), while a recent report by Scott et al (2013) documented the first case of resistance to monepantel, a novel drug-class which has only been commercially available since 2009.…”
Section: Introductionmentioning
confidence: 99%
“…The EHT has been used as an in vitro test for the detection of BZ resistance in previous studies using different TBZ concentrations to calculate the ED 50 [16][17][18]; however, in the present study we used a single DD as a simpli ed form of the test. According to our results, the percentage of resistant ocks in the northwest of Spain during 2015-2016 was 35% by FECRT or 26% by EHT.…”
Section: Discussionmentioning
confidence: 99%